BATAS WILAYAH DAN DINAMIKA PENJAGAAN BATAS LAUT DI INDONESIA DALAM DIMENSI SOSIOKULTURAL - Marsetio, Marsetio (HUMANIKA, 2013)
ABSTRACT This paper discusses about boundaries concept and the dynamics of sea boundaries in Indonesian. As an archipelagic state with a very potential resources, unfortunately Indonesia does not have an "Ocean Policy" concept as a guide to build a maritime state. Especially about the security of Indonesian sea boundaries in remote island. Yet as a country that has a long maritime history, Indonesia has a lot of lessons as a basis for understanding the substance that determines the orientation of the maritime glory and decline of Indonesia from time to time. Keywords: ocean policy, maritime state, sea boundaries, remote island.